Location-allocation of public services – Citizen access, transparency and measurement. A method and evidence from Brazil and Sweden. (September 2017) - Fredriksson, Anders
Abstract: Access to public services is an important determinant of economic opportunities and well-being. We argue that location-allocation analysis can be used not only to determine the optimal spatial allocation of public services, but also as a tool to increase transparency in the allocation decisions. We illustrate by analyzing Citizen Service Centers in Brazil and Sweden. We first show how the optimal spatial allocation of such centers can be obtained with data that is largely publicly available, which allows for transparency. Based on the suggested optimum, we then introduce different public services misallocation metrics, beyond what the literature has previously discussed. We show how such misallocation metrics can be related to socioeconomic outcomes and political- and other variables, thus suggesting a method that can become a useful tool in analyses of public sector performance. Highlights: We analyze the spatial access to public services. A transparent method, using data that is largely publicly available, is suggested. A misallocation metric of public services is introduced. The method can be used for transparent comparisons of access to public services for different regions and countries.